2006
DOI: 10.1103/physrevlett.96.067205
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Vortex Core Dynamics in Cylindrical Ferromagnetic Dots

Abstract: We report direct imaging by means of x-ray photoemission electron microscopy of the dynamics of magnetic vortices confined in micron-size circular Permalloy dots that are 30 nm thick. The vortex core positions oscillate on a 10-ns timescale in a self-induced magnetostatic potential well after the inplane magnetic field is turned off. The measured oscillation frequencies as a function of the aspect ratio (thickness/radius) of the dots are in agreement with theoretical calculations presented for the same geometr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
167
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(180 citation statements)
references
References 26 publications
10
167
0
3
Order By: Relevance
“…9 The existence of such critical velocity (u c =250 m/s for permalloy dots) was recently confirmed by time-resolved magnetic scanning transmission x-ray microscopy 46 for vortex core reversal in FeNi dots. We used in Figs.…”
Section: Nonlinear Effects and Vortex-core Reversalmentioning
confidence: 92%
See 1 more Smart Citation
“…9 The existence of such critical velocity (u c =250 m/s for permalloy dots) was recently confirmed by time-resolved magnetic scanning transmission x-ray microscopy 46 for vortex core reversal in FeNi dots. We used in Figs.…”
Section: Nonlinear Effects and Vortex-core Reversalmentioning
confidence: 92%
“…The nonlinear coefficients can also be calculated within the pole-free model, 9,17 and their signs are /?>0, <5>0. The linear response coefficient is £=2/(3/?)…”
Section: Notation If H(t)=h 0 E'"" Then H(t)=h(t)m S Vmentioning
confidence: 99%
“…This dynamic behavior has been explained as the movement of the vortex core in its self-induced magnetostatic restoring force. 3 The eigenfrequency of the gyration mode typically lies in the subgigahertz range and is dependent on the size of the structure. For disk-shaped structures, it has been theoretically and experimentally found that for given material parameters, the gyration frequency approximately scales with the geometrical aspect ratio, with only a slight dependence on the thickness and lateral size separately.…”
Section: Introductionmentioning
confidence: 99%
“…The vortex magnetization distribution stability as well as the vortex excitations were studied in Refs. [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%